Are under- and overweight female elite athletes thin and dat? A controlled study - Klungland Torstveit, M.; Sundgot-Borgen, J. (Medicine & Science in Sports & Exercise, 2012)
Purpose: The study`s purpose was to relate body mass index (BMI) to body fat percentage as measured by dual-energy x-ray absorptiometry in female elite athletes from different sports and nonathletic controls and to investigate what characterizes the athletes with unhealthy low and high body fat values.